Anatomical versus Nonanatomical Resection in Patients with Hepatocellular Carcinoma Located in the Left Lateral Segment. Issue 11 (November 2013) - Sasaki, Kazunari; Matsuda, Masamichi; Ohkura, Yu; Hashimoto, Masaji; Watanabe, Goro
To date, no reported studies comparing anatomical resection (AR) and nonanatomical resection (NAR) for hepatocellular carcinoma (HCC) have restricted cases by tumor location. Thus, right hepatectomy and left lateral sectionectomy are both analyzed together as AR, whereas limited resection of both peripherally and centrally located liver tumors is categorized as NAR. This categorization may result in inaccurate conclusions in the analyses comparing AR and NAR. We conducted a retrospective comparison between AR (n = 30) and NAR (n = 57) for solitary and small (5 cm or less) HCC limited to the left lateral segment (LLS) to clarify whether AR is superior to NAR for HCC in LLS. The 1-, 3-, and 5-year recurrence-free survival rates were 83.3, 71.3, and 52.9 per cent for the AR group and 82.5, 51.0, and 40.7 per cent for the NAR group, respectively ( P = 0.10). The 3-, 5-, and 7-year overall survival rates were 96.0, 82.8, and 77.9 per cent for the AR group and 84.1, 77.0, and 54.2 per cent for the NAR group, respectively ( P = 0.07). The postoperative complication, recurrence patterns, and secondary treatment types after recurrence were not significantly different between the two groups. The multivariate analysis including the confounders related to background liver function indicated AR to be a significant protective factor against recurrence, although AR did not influence overall survival. AR was superior to NAR in preventing recurrence without increasing postoperative risks among patients with small solitary HCC limited to the LLS, although AR could not improve overall survival.